Effect of ultrasound-assisted aqueous enzymatic extraction on the interfacial properties of high-oleic peanut oil bodies - Leixi Wang; Liang Liu; Ni Pang; Wei Li; Wanhua Guo; Runxuan Zhang; Guihuan Wei; Lei Dai; Qingjie Sun; Xuyan Dong (Grain & Oil Science and Technology)
Oil bodies (OBs) are the lipid-storage organelle in oilseed, and their interface properties are crucial for oilseed processing. To elucidate the effect of interfacial proteins on the functional properties of high-oleic and normal peanut OBs, OBs were extracted using ultrasound-assisted aqueous enzymatic extraction (AEE), and the effects of ultrasonic power (100–500 W) and extraction time (0–30 min) on the interface properties were investigated. These results indicate that the interfacial protein content and interface properties of OBs can be significantly affected by ultrasonic treatment. The interfacial protein content of high-oleic peanut OBs increased from 88.25% to 91.95% after ultrasonic treatment, which was 1.4 times that of normal peanuts OBs. The emulsifying activity index (EAI) and emulsion stability index (ESI) values of both peanut OBs increased with the increase in ultrasonic power and extraction time. These results suggest that the emulsification ability of OBs may be closely related to the interfacial protein content and therefore can be regulated by altering the interfacial protein content using ultrasonic treatment. However, the particle size of OBs tends to increase under low ultrasonic power (0–200 W) owing to the increase in the interfacial protein content and aggregation effects, whereas it decreases under high ultrasonic power (300 W–500 W) due to cavitation effects. This pattern of change in particle size was also confirmed by confocal laser scanning microscopy, which indicated that high ultrasonic power suppressed the contribution of the interfacial protein content to the particle size, but still improved the emulsification ability of the OBs by reducing the particle size and increasing the interfacial tension. Therefore, regulating the interfacial protein content of peanut OBs by adjusting ultrasonic power is a promising way to improve their functional properties.